Our world of mysteries ; fascinating facts about the planet earth - Lord, Suzanne (New York : Scholastic, 1991)
From the ocean abyss, where odd creatures live in complete darkness, to the Anasazi people, who vanished from the Earth, leaving only ancient apartments behind, readers will discover some of the earth's strangest places and most fantastic mysteries in this literary adventure.
Z
930
Z
Keywords: Natural history